Pengembangan LKPD Fisika Berbasis Case Based Learning (CBL) - Reka Putri; Tri Ariani; Ovilia Putri Utami Gumay (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
Physics instruction requires teaching materials that can help students understand the subject matter actively and contextually. One approach that can be taken is to develop student worksheets (LKPD) based on Case-Based Learning (CBL). This study aims to develop physics student worksheets based on Case-Based Learning that are suitable for use as teaching materials in physics instruction. This study is a research and development (Research and Development) project using the 4D development model according to Siahaan (2025), which includes the define, design, develop, and disseminate stages. This study was limited to the develop stage. The feasibility of the product was assessed by one subject matter expert, one media expert, and one language expert using a validation sheet. The results showed that the developed worksheets received a validation percentage of 93.3% from the subject matter expert, 87.2% from the media expert, and 89.3% from the language expert, all of which fell into the “highly valid” category. These results indicate that the physics worksheets based on Case-Based Learning have met the feasibility criteria as instructional materials. Thus, the developed worksheets can be used as an alternative instructional resource in physics education.